PENGARUH WORK-LIFE BALANCE, SELF EFFICACY, DAN JOB INSECURITY TERHADAP KINERJA KARYAWAN PR. ALFI PUTRA TRENGGALEK - Diyah Maharani; Siti Mujanah (Cahaya Ilmu Bangsa, 2025)
This research was conducted in order to analyze and prove whether there is an influence and measure how strong the relationship of work-life balance, self efficacy, and job insecurity on the performance at PR. Alfi Putra Trenggalek. The type of research is explanatory research based on quantitative methodology. Explanatory research requires clarification of the relationship between research variables and the hypothesis testing process. Quantitative methodology is implemented in the analysis methodology. Production employees at PR Alfi Putra are the population in this study with a sample of 80 people. The main source of initial data comes from primary data, namely questionnaires. The methodology used to analyze the data includes: validity and reliability tests, normality tests, multicollinearity, and heteroscedasticity, multiple linear regression analysis, correlation tests (R), coefficient of determination tests (R2), t and F hypothesis tests. The findings partially prove that the work-life balance and self efficacy variables have a positive and significant influence on the employees performance of PR Alfi Putra Trenggalek, whereas job insecurity has a significant negative effect on the employees performance of PR Alfi Putra Trenggalek. Meanwhile simultaneous testing, work-life balance, self-efficacy, and job insecurity proves to have a significant effect on the employees performance of PR. Alfi Putra Trenggalek. Based on these results, it is important for companies to reduce job insecurity through clear work contracts and open communication. Penelitian ini dilakukan guna untuk menganalisis dan membuktikan apakah terdapat adanya pengaruh serta mengukur seberapa kuat hubungan dari work-life balance, self efficacy, dan job insecurity terhadap Kinerja Karyawan PR. Alfi Putra Trenggalek. Jenis penelitian merupakan penelitian eksplanatori berbasis metodologi kuantitatif. Penelitian eksplanatori memerlukan klarifikasi hubungan antara variabel penelitian dan proses pengujian hipotesis. Metodologi kuantitatif diimplementasikan dalam metodologi analisis. Karyawan produksi di PR Alfi Putra merupakan populasi dalam penelitian ini dengan sampel sebanyak 80 orang. Sumber utama data awal adalah bersumber dari data primer yaitu kuesioner. Metodologi untuk mnganalisis data yang digunakan meliputi: pengujian validitas dan reliabilitas, pengujian normalitas, pengujian multikolinieritas dan heteroskedastisitas, analisis regresi linier berganda, analisis korelasi (R), koefisien determinasi (R2), pengujian hipotesis t dan F. Hasil temuan membuktikan pengujian parsial variabel work-life balance dan self efficacy berpengaruh positif dan juga signifikan terhadap kinerja karyawan PR Alfi Putra Trenggalek, sedangkan job insecurity bepengaruh negatif signifikan terhadap kinerja karyawan PR. Alfi Putra Trenggalek. Sementara itu pengujian simultan work-life balance, self efficacy, dan job insecurity membuktikan berpengaruh signifikan terhadap kinerja karyawan PR. Alfi Putra Trenggalek. Atas hasil tersebut, penting bagi perusahaan untuk mengurangi job insecurity melalui kontrak kerja yang jelas serta komunikasi yang terbuka.